Analisis Laporan Keuangan: Analisis Rasio Terhadap 4 Perusahaan Makanan Dan Minuman Yang Tercatat Di Bei - Desfi Dwi Sulistyana; Erinda Aprilia Puspitasari; Mei Liana Rofilia Sari; Rr Adzkia Larasati Meyrizky; Cholis Hidayati (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research was conducted to show and analyze the financial ratios of 4 companies in the food and beverage sector, namely PT. Diamond Food Indonesia Tbk., PT. Ultrajaya Milk Industry & Trading Company Tbk., PT. Indospring Tbk, & PT. Coca Cola Tbk. during the period 2020 to 2022 to see how the company will perform in the future. The type of research carried out is descriptive research using data analysis, namely financial ratio analysis. Research was also carried out through the official website of the Indonesian Stock Exchange (BEI). The data source used is secondary data. The data collection technique in this research is documentation. The results of this financial ratio analysis will consist of liquidity ratios, solvency ratios, activity ratios and profitability ratios